Bisexuality and Suicide: A Systematic Review of the Current Literature. (1st August 2014) - Pompili, Maurizio; Lester, David; Forte, Alberto; Seretti, Maria Elena; Erbuto, Denise; Lamis, Dorian A.; Amore, Mario; Girardi, Paolo
Abstract: Introduction: Many studies of lesbian, gay, and bisexual youth have demonstrated that individuals reporting a bisexual orientation have a particularly high risk of suicidal behavior and substance abuse. It has been also suggested that bisexual individuals (both men and women) have higher rates of depression and anxiety compared with homosexual and heterosexual groups. Aim: The aim of the present article was to determine whether or not an association between bisexuality and suicidal behavior exists and to analyze risk factors for suicidal behavior in bisexual individuals. Main Outcome Measures: The combined search strategies yielded a total of 339 records screened from PubMed, Scopus, and Web of Knowledge. Duplicate articles, articles that were not in English, and those that did not analyze bisexuality separately from homosexuality were excluded. A quality assessment was performed for each study included. Methods: A careful systematic review of the literature was conducted investigating the potential bisexuality‐suicidal behavior link. A total of 77 articles from peer‐reviewed journals were considered, and the most relevant (N = 19) were selected for this review. Results: Individuals reporting a bisexual orientation had an increased risk of suicide attempts and ideation compared with their homosexual and heterosexual peers. Risk factors included related victimization, peer judgments, and family rejection. Bisexual individuals also reported higher rates of mental illness and substance abuse. Conclusions: Bisexual individuals may experience more psychological distress and mental health problems than individuals who identify with a homosexual or heterosexual orientation. Clinicians should consider the potential for suicidal behaviors in bisexual individuals and be alert for increased mental health problems and poor social integration.